Leukocytosis and neutrophilia predicts outcome in anal cancer. Issue 1 (January 2017) - Schernberg, Antoine; Escande, Alexandre; Rivin Del Campo, Eleonor; Ducreux, Michel; Nguyen, France; Goere, Diane; Chargari, Cyrus; Deutsch, Eric
Abstract: Objective: Leukocytosis and neutrophilia could be the tip of the iceberg in the inflammatory tumor microenvironment. We aimed to validate their prognostic significance in a cohort of patients treated with definitive chemoradiation for anal squamous cell carcinoma (SCC). Materials & methods: Clinical records from all consecutive patients treated in a single institution between 2006 and 2016 with curative-intent radiotherapy were retrospectively analyzed. Leukocytosis and neutrophilia, defined as leukocyte or neutrophil count over 10, 000 and 7500/mm 3, respectively, were studied in terms of overall survival (OS), progression (PFS), locoregional (LFS) and distant (DFS)-free survival. Results: We identified 103 non-metastatic HIV-negative patients, with concurrent chemotherapy use in 78%. Twelve and 8% displayed baseline leukocytosis and neutrophilia, respectively. Estimated 3-year OS and PFS were 88% and 67%, respectively. In univariate analysis, both leukocytosis and neutrophilia were strongly associated with inferior OS, PFS, LFS and DFS ( p  < 0.01). In multivariate analysis, leukocytosis and neutrophilia remained strongly associated with patient outcome ( p  < 0.01), independently from tumor T and N-stage. Anemia was an independent predictor of worse OS and PFS, while chemoradiation overall treatment time below 50 days improved PFS. Conclusion: Leukocytosis and neutrophilia are strong prognostic factors for OS, PFS, LFS and DFS in anal cancer treated with chemoradiation. These biomarkers could help identify patients with higher risk of tumor relapse that require treatment intensification.